Performance in public organizations: clarifying the conceptual space - Andersen, Lotte Bogh; Pedersen, Lene Holm; Boesen, Andreas (2016)
Performance in public organizations is a key concept that requires clarification. Based on a conceptual review of research published in 10 public administration journals, this article proposes six distinctions to describe the systematic differences in performance criteria: From which stakeholder's perspective is performance being assessed? Are the criteria formal or informal? Are the criteria subjective? Which process focus and product focus do they have, if any? What is the unit of analysis? Based on these distinctions, the performance criteria of existing studies used in an empirical review of management and performance are classified. The results illustrate how a systematization of the conceptual space of performance in public organizations can help researchers select what to study and what to leave out with greater accuracy while also bringing greater clarity to public debates about performance. - Reproduced.
Keywords: Performance appraisal